Role of Credit Co-operatives in the Agricultural Development of India - Uma Devi, R (Journal of Commerce and Trade, 2011)
Agricultural development is essential for the overall development of any country for which credit is an essential input. Due to the disadvantages of non-institutional sources, the GOI launched various financial institutions in order to provide adequate, cheap and timely credit to the needy farmers. In the context of liberalization, privatization and globalization of the Indian economy, Cooperatives are recognized as the only institutions, which may improve the quality of rural households. On this backdrop, an attempt is made to analyze the role of credit cooperatives in the agricultural development of India.